What do tropical cryptogams reveal? Strong genetic structure in Amazonian bryophytes. Issue 2 (6th July 2020) - Ledent, Alice; Gauthier, Jérémy; Pereira, Martinha; Overson, Rick; Laenen, Benjamin; Mardulyn, Patrick; Gradstein, S. Robbert; de Haan, Myriam; Ballings, Petra; Van der Beeten, Iris; Zartman, Charles E.; Vanderpoorten, Alain
Summary: Lowland tropical bryophytes have been perceived as excellent dispersers. In such groups, the inverse isolation hypothesis proposes that spatial genetic structure is erased beyond the limits of short‐distance dispersal. Here, we determine the influence of environmental variation and geographic barriers on the spatial genetic structure of a widely dispersed and phylogenetically independent sample of Amazonian bryophytes. Single nucleotide polymorphism data were produced from a restriction site‐associated DNA sequencing protocol for 10 species and analyzed through F‐statistics and Mantel tests. Neither isolation‐by‐environment nor the impact of geographic barriers were recovered from the analyses. However, significant isolation‐by‐distance patterns were observed for 8 out of the 10 investigated species beyond the scale of short‐distance dispersal (> 1 km), offering evidence contrary to the inverse isolation hypothesis. Despite a cadre of life‐history traits and distributional patterns suggesting that tropical bryophytes are highly vagile, our analyses reveal spatial genetic structures comparable to those documented for angiosperms, whose diaspores are orders of magnitude larger. Dispersal limitation for tropical bryophytes flies in the face of traditional assumptions regarding their dispersal potential, and suggests that the plight of this component of cryptic biodiversity is more dire than previously considered in light of accelerated forest fragmentation in the Amazon.